A Southern White Clergyman, the Freed People, and the Nineteenth-Century Episcopal Church - Mead, Loren B. (Journal of Anglican studies, 2024)
Reared in antebellum South Carolina, Peter Fayssoux Stevens was a typical white southerner until Reconstruction. He came of age in the 1840s and 1850s and fought for the Southern Confederacy during the Civil War. Before his military service commenced in 1861, he was ordained a priest in the Protestant Episcopal Church (PEC) of North America. After Appomattox, as Black communicants deserted white Protestant churches in droves, Stevens believed that they might return to the PEC if they could choose their leaders and decide fundamental questions affecting their parishes. When white church leaders refused to follow Stevens’s recommendations, he left the PEC and joined the Reformed Episcopal Church (REC). He spent more than four decades after the war ministering to Black communicants. Although Stevens was not a champion of civil rights, his career provides a compelling case study of a white clergyman who evolved from a traditional southerner and zealous Confederate soldier to an advocate for Black communicants in the church.